Effects of national energy policies on carbon dioxide emissions in a European internal electricity market: Results from a simulation model of the European power systems - Frank Hoster (Fondazione Eni Enrico Mattei (FEEM), 1997)
This article considers the economic and environmental (in terms of CO2) effects of national energy policies in a European Single Market for electricity. It was found that the combined CO2/Energy-tax proposed by the European Commission would be able to stabilise the current volume of CO2-emissions in the electricity sector. A national single handed effort in introducing a CO2-tax to reduce the emissions was found to be ineffective in the long term and would be in addition allocative inefficient accompanied with macroeconomic disadvantages for the country riding ahead. It was also found that reduction targets can be achieved in an Internal Market with a lower tax rate than in the current system.
Keywords: Q4; C61; F21; 330; Linear Programming Model; European Power Systems; Interregional electricity trade; Carbon dioxide abatement; Elektrizitätsversorgung; Nachhaltige Energieversorgung; Treibhausgas-Emissionen; Luftreinhaltung; Mathematische Optimierung; Theorie; EU-Staaten